Att tolka tegel: En studie av byggnadstekniken i Heliga korsets kyrka i Hattula - Ratilainen, Tanja (Hikuin, 2003)
Research On the Building Technique of St Cross Church of Hattula in Häme By Tanja Ratilainen The main object of the research was to see what kind of building technique was used and how the building process had proceeded in the 15th century when the St Cross Church of Hattula was built. In addition, it was to see if the building technique could give some proof of the debated issue on whether the Hattula Church was built in a single building phase or not. Firstly, I had to define the original medieval masonry. In doing so, I discovered some new facts about the repairs that had been done during the long history of the church. Secondly, the research of the building technique resulted in a number of interesting facts about the wedges, bonding technique, scaffolding and the lifting levels of the masonry. Thirdly, the vertical joints hint that the bricklayers proceeded from the east end of the nave towards the west end and from the gable ends of the sacristy and the porch towards the nave. Fourthly, it is probable that the same groups of bricklayers had worked on the different parts of the church, the nave, the sacristy and the porch. Therefore, this result combined with other evidence suggests that the church was built in many stages within one single building phase.